2021
DOI: 10.1371/journal.pone.0252336
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of national-level natural resource rents on life expectancy: A cross-country panel data analysis

Abstract: While a substantial amount of literature addresses the relationship between natural resources and economic growth, relatively little is known regarding the relationship between natural resource endowment and health at the population level. We construct a 5-year cross-country panel to assess the impact of natural resource rents on changes in life expectancy at birth as a proxy indicator for population health during the period 1970–2015. To estimate the causal effects of interest, we use global commodity prices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
5
8
0
Order By: Relevance
“…Besides, the directional relationship between GDP growth and total natural resources rents seems consistent with the study of Lyatuu et al (2021). They indicated that an increase in resource rents leads to a substantial increase in government income in the short term, which can transpose into government spending.…”
Section: Discussionsupporting
confidence: 79%
“…Besides, the directional relationship between GDP growth and total natural resources rents seems consistent with the study of Lyatuu et al (2021). They indicated that an increase in resource rents leads to a substantial increase in government income in the short term, which can transpose into government spending.…”
Section: Discussionsupporting
confidence: 79%
“…But we nd no reason to believe the global growth rate increases health except through economic effects in the resource extracting countries. This replication allows us to assess how much Lyatuu et al's (Lyatuu et al, 2021) results agree with ours. The commodity price index is the equally weighted average of the price index for agricultural goods, energy, and minerals and metals (including precious metals) taken from the International Monetary Fund´s (IMF) database (see https://www.imf.org/en/Research/commodity-prices).…”
Section: Methods and Datasupporting
confidence: 71%
“…Our data setup and method differ from one recent study that shows energy and mineral resource dependency positively affects life expectancy (Lyatuu et al, 2021), using basic life expectancy data, not HALE as we do. They estimated the ratio of resource rents to GDP on life expectancy in a two-way, xedeffects setup using a two-stage instrumental-variables estimation strategy.…”
Section: Methods and Datamentioning
confidence: 87%
See 2 more Smart Citations